STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN PELAYANAN AUTO RITZ BAUBAU - Yuni Hapsari (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2023)
This research aims to find out the marketing communication strategy in improving the service of Auto Ritz Baubau and to find out the obstacles of marketing communication strategy in improving the service of Auto Ritz Baubau. The research medote used is qualitative with a descriptive approach that aims to describe the object or variable under study, through an induction process, with empirical observations through observation and in-depth interviews and documentation. Data analysis techniques used in this research include transcripts of interview results, data reduction, analysis, data interpretation and triangulation. The results showed that Auto Ritz Baubau has implemented a marketing communication strategy that focuses on giving a positive impression, friendly approach, and satisfying service. Responses to customer complaints by listening, showing empathy, and responding quickly are good steps to maintain customer satisfaction. However, the obstacle lies in the lack of promotion, especially through social media, which can affect consumers' understanding of the advantages of products and services. Product completeness and weaknesses in public speaking are also aspects that need attention. By overcoming promotional barriers and improving formal communication, Auto Ritz Baubau can strengthen its corporate image and increase customer appeal.